Rancang Bangun Rekaman Gerak Kendaraan pada Sepeda Motor untuk Data Investigasi Kecelakaan Lalu Lintas Berbasis Modul GSM - Aziz Ariono Rahman; Ridho Hendra Yoga Perdana; Martono Dwi Atmadja (Politeknik Negeri Malang, 2020)
Motorcycle are movable objects that become public transportation needs. Motorcyclists include people from various backgrounds have experienced accidents. One of the causes of accidents is the speed. Motorcycle that has accident will fall and get injured. The need to know the cause of the accident requires investigation and analysis. Data needed to analyze traffic accidents such as vehicle operating speed and location of the accident. Required data can be obtained by utilizing infrared sensor as motorcycle speed sensor, gyroscope sensor for indicators of falling or not motorcycle and GPS to determine the coordinate points of movement motorcycle. This information is communicated using GSM module. The information is sent to the database and then displayed via Android application and the data log is stored on smartphone storage. Based on the results of tests carried out, it is known that accuracy of the speed sensor readings is 98.39% from 12 tests. The GPS test tool compared to Garmin GPS has an average difference of 3.14158 meters. The fall indicator can function properly when falls and the data can be viewed via Android application. The data is stored on smartphones and in firebase storage. The average delay test is 7,087 seconds.